(untitled) (The Journal of Plant Protection Sciences, 2023)
Application of biocontrol agent can be done in three ways (i) seed treatment, (ii) soil treat ment and (iii) foliar spray. Seed treatment has been considered the most convenient of the three as it is required in less amounts with higher efficacy. Seed being an essential com ponent of agriculture acts as a passive carrier of many diseases. Seed treatment with bio control agents may serve as an important tool for managing many soil-borne and seed borne diseases. This process is known as ‘biopriming’. Goals for biological seed treat ment include control of soil borne pathogens, colonization and protection of subterranean plant parts, and increased plant growth. Effec tive biocontrol agents have been developed for control of severe seed and seedling patho gens. Several researchers have reported the biological seed treatments for the protection of seed and control of pathogens causing seedling diseases (1,15,3). Similarly several scientists have got positive results of disease control and increased plant growth and yield in vivo and under field condition (6,4,2,11). The efficacy of biological seed treatment is influenced by soil pH and iron concentration (14), moisture, temperature and inoculums density of the pathogen (9). Trichoderma spp.